Managing conflict resolution (London : Cambridge Educational, 2011)
Beginning with the notion that we deal with conflict largely through patterns learned as children, the program explores four behaviors that push conflict into the destructive zone: miscommunication, demonizing, refusal to negotiate, and'kitchen sinking' or pulling past events and unrelated frustrations into a present disagreement. The pitfalls of a'conflict loop' are also discussed. Viewers gain an understanding of the potential rewards of recognizing an opponent's needs as well as one's own. Mediation, including peer mediation and the'third side' method of negotiation, is examined
DVD format
Keywords: Conflict management; Social conflict; Conflict (Psychology).